Exploring the Relationship Between Leadership and Job Satisfaction of Bank Mandiri Employees - Annisa Findarty (Arthatama: Journal of Business Management and Accounting, 2025)
Leadership significantly influences employee job satisfaction, shaping a productive work environment and supporting organizational success in the competitive banking sector. This study aims to examine the relationship between leadership styles and employee job satisfaction at Bank Mandiri, a leading Indonesian bank, by analyzing how leadership practices impact employee well-being and retention. The research employed a Systematic Literature Review, analyzing 30 peer-reviewed journal articles published between 2019 and 2024, sourced from databases like Scopus and ScienceDirect. The findings reveal a strong positive correlation between transformational and participative leadership styles and employee job satisfaction, driven by open communication, recognition, and employee involvement in decision-making. In contrast, authoritarian leadership often reduces satisfaction due to limited autonomy. These results highlight the importance of adaptive leadership in fostering a motivated workforce. The study concludes that Bank Mandiri should prioritize leadership training programs focusing on transformational and participative approaches to enhance employee satisfaction and organizational performance. By addressing these leadership practices, the bank can strengthen its human resource management strategies, ensuring a balance between achieving business goals and promoting employee well-being in a dynamic industry.